2023
DOI: 10.1039/d2re00408a
|View full text |Cite
|
Sign up to set email alerts
|

Modeling-aided coupling of catalysts, conditions, membranes, and reactors for efficient hydrogen production from ammonia

Abstract: The production of high-purity, pressurized hydrogen from ammonia decomposition in a membrane catalytic reactor is a feasible technology. However, because of the multiple coupled parameters involved in the design of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The result from their study showed that the rate of reaction is first-order dependent over the entire temperature and pressure range which is different compared to other studies [14]. Realpe et al determined that the optimization of hydrogen production cannot rely upon only one factor, such as the catalyst, by developing a dimensionless model of the membrane reactor [18]. The approach to improve the conversion of NH 3 needs to be all-rounded yet not only focused on the catalyst, as the conversion of NH 3 is also affected by the presence of a hydrogen-selective membrane.…”
Section: Literature Reviewmentioning
confidence: 82%
“…The result from their study showed that the rate of reaction is first-order dependent over the entire temperature and pressure range which is different compared to other studies [14]. Realpe et al determined that the optimization of hydrogen production cannot rely upon only one factor, such as the catalyst, by developing a dimensionless model of the membrane reactor [18]. The approach to improve the conversion of NH 3 needs to be all-rounded yet not only focused on the catalyst, as the conversion of NH 3 is also affected by the presence of a hydrogen-selective membrane.…”
Section: Literature Reviewmentioning
confidence: 82%
“…27 In this regard, we recently showed through extensive experimental data fitting for various catalysts that a non-Temkin-Pyzhev kinetic expression containing the equilibrium constant can represent the reaction kinetics for the high-pressure production of H 2 . 28 To unravel the disparity related to the RDS, each catalytic system needs a closer look using multiple approaches above and beyond the classical Temkin-Pyzhev model. 29 The problem of misidentifying the RDS also goes hand in hand with regarding N as the most abundant reaction intermediate, which contrasts with the observations of several modeling studies.…”
Section: Introductionmentioning
confidence: 99%
“…27 In this regard, we recently showed through extensive experimental data fitting for various catalysts that a non-Temkin–Pyzhev kinetic expression containing the equilibrium constant can represent the reaction kinetics for the high-pressure production of H 2 . 28…”
Section: Introductionmentioning
confidence: 99%